DESAIN APLIKASI PEMESANAN MAKANAN RESTORAN PONDOK KERANG BERBASIS ANDROID MENGGUNAKAN AUGMENTED REALITY - Dandi, Afri; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2024)
Research focuses on the design of an Android-based food ordering application, emphasizing the visualization of 3D menu objects using Augmented Reality (AR) technology. The primary objective is to enhance the user experience through immersive visualizations of menu items. The application intentionally excludes additional features such as online payment, restaurant menu management, or online purchasing integration, maintaining a streamlined focus on augmented reality-enhanced food ordering. The compatibility of the application spans from Android version 8.0 to version 13.0, ensuring accessibility to a wide range of Android users. The research targets a specific set of 9 food items and 4 beverage items in the menu. The implementation utilizes the C# programming language, providing a robust and versatile foundation for the application's development. EasyAR SDK serves as the chosen platform for markerless augmented reality development, ensuring efficient and dynamic visualizations of 3D menu items within the application.